ASSESSING WIND ACCURACY IN A COUPLET ATMOSPHERE-WAVE SYSTEM FOR THE NORTHEAST COAST OF BRAZIL - Bose, Nícolas de Assis; Reis, Jean Souza dos; Dantas, Vanessa de Almeidas; Amorim, Ana Cleide Bezerra; Matos, Maria de Fátima Alves de; Emiliavaca, Samira de Azevedo Santos; Oliveira, Leonardo de Lima; Bezerra, Luciano Andre Cruz; Farina, Leandro (Anais Congresso Brasileiro de Energia Solar - CBENS, 2024)
This paper investigates the sensitivity of offshore wind simulations, focusing on the northeast coast of Brazil. The study utilizes the Coupled Ocean-Atmosphere-Wave-Sediment Transport Modeling System (COAWST), integrating the Weather Research and Forecasting (WRF) and Simulating Waves Nearshore (SWAN) models. The research emphasizes the impact of wind-wave interaction on wind speed, considering factors such as atmospheric and ocean surface conditions. The methodology includes site selection, model overview, and validation techniques. Results indicate that the coupled atmosphere-wave model outperforms the stand-alone atmospheric model, showcasing enhanced accuracy in predicting wind speed. The paper discusses the significance of considering wave effects in offshore wind modeling and provides insights into the interplay between wind and waves, emphasizing the need for precise simulations in wind energy assessments.